Energy Awareness and Conservation Behavior of Russian Residential Households - ANISIMOVA, T. Yu.; SADRIEV, A. R. (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016, 2017)
The programme aimed at the increase of energy efficiency of the economy has been implemented in Russia in the last 10 - 15 years. The corresponding regulatory base and energy-saving programmeswere worked out at both national and republic levels. The results of this programme were sufficient up to 2008. However, rather insignificant changes have taken place in Russian energy efficiency sincethe world financial crisis of 2008. So, it is impossible to speak about any positive tendencies. It means that energy-wasting activities, taking place all over the country, exceed the positive effects of energy savingby enterprises. It is partly due to the population of Russia that comprises 150 million people. According to the research, 68% of urban populationhas no ideas about management of energy consumption in their households, and 54% of urbanpeopleare not going to do it in the perspective. As a result of the research, different activities, aimed at promotionof energy efficiency, were proposed. We hope that the realization of these activities will facilitate the increase of energy efficiency of our country and, thus, the increase of the quality of the world ecosystem.